Monitoring accumulative fatigue and recovery status in elite field hockey players during different phases of a competitive season - De Villiers, L. A. (2014)
There is a lack of research in the sport of field hockey, specifically where monitoring of fatigue and recovery is concerned. The primary aim of the study was thus to monitor the accumulative fatigue and recovery state of elite field hockey players during the different phases of a competitive season. The specific objectives of the study were to determine the changes in heart rate recovery of elite hockey players; to determine the changes in perceptual fatigue; to determine the relationship between players` perceptions of recovery and stress; and to determine the relationship between the objective and subjective measures of recovery and fatigue over different phases during a competitive season. Elite female hockey players (n = 15) from Stellenbosch University were monitored over 23 weeks. This group comprised of players from the first team (Maties) and second team (VICS) of the club. The following tests were administered: the Heart rate Interval Monitoring System (HIMS) test with the use of SUUNTO heart rate monitors and SUUNTO Team Manager, the Perceptual Fatigue questionnaire (on a weekly basis), and the Recovery-Stress Questionnaire for Athletes (RESTQ-Sport 76) (during each phase of their normal competition cycle). There were a number of significant findings (p<0.05) relating to the aim and objectives of the study. One of the main findings was that there were significant differences between the phases with regard to the measured variables. Players experienced significantly more Fatigue, Lack of Energy and Pressure during the first Competition phase. With regard to the HIMS, players performed the best during the second Competition phase, following the university holidays. Even though not all the differences were statistically significant, collectively the results indicate that these monitoring tools can be used for teams. An added advantage with all three monitoring tools is that each person can be used as their own baseline. In a team setting it gives the coach and support team the opportunity to individualise training programmes and recovery methods.